Two new species of the genus Stenommatus Wollaston, 1873 (Coleoptera: Curculionidae: Dryophthorinae; Dryophthorini) from Peru - Legalov, Andrei A. (2019)
The weevil tribe Dryophthorini is reported in Peru for the first time. Two species from Satipo, Junin, Stenommatus chabooae Legalov n. sp. and Stenommatus sokolovi Legalov n. sp., are herein described. Stenommatus chabooae Legalov n. sp. is characterized by having the elytral interstriae narrower than striae width; pronotum coarsely punctate; large, narrow aedeagus, weakly curved at apex, with a large basal sclerite of the endophallus. Stenommatus sokolovi is characterized by having the elytral interstriae as wide as striae width; pronotum finely punctate; small, wide aedeagus, rounded at apex and endophallus lacking sclerites. A key to the South American species of the genus Stenommatus is given.